Improvement of the reverse characteristics of Schottky diodes using gettering - Litvinenko, V.N.; Vikulin, I.М.; Gorbachev, V.E. (Технология и конструирование в электронной аппаратуре, 2019)
The paper considers the causes and mechanisms of the influence of defects and impurities on the reverse current of the Schottky diode. The influence of two getter regions, which were created by different technologies on the working side and the reverse side of the plate, on the value of the reverse current of diodes was experimentally investigated, and the physical factors of such influence were analyzed. The proposed technology for creating getter regions allows one to significantly reduce the reverse current of diodes and increase the product yield.